A Study of EFL Learners: Student Team Achievement Division Method in Increasing Students' Argumentative Text Writing - Fitriana, Meida; Yusup, Mohamad (JEdu: Journal of English Education, 2025)
English has become a necessity for everyone to be able to communicate in today's global era.  This study aimed to identify the application of the Student Team Achievement Division (STAD) learning method to improve the ability to write argumentative text in fifth-semester students of STISIP Banten Raya. This research was a descriptive qualitative research and the object of this research is 28 students of STISIP Banten Raya Pandeglang. In learning English there are four skills that must be possessed, namely listening, reading, writing, and speaking skills. In STAD method there is one component that must be implemented, namely team formation, student are organized based on their pre-test result. Each team consists of from three students with different level English proficiency such as high, medium, and low proficiency. Thus forming a team with heterogeneous member abilities is a best choice. The research instruments used were tests and observations. The test used as a pre-test and post- test. Students worked in a team and assisted each other in learning the assigned material. All team members had to sign the worksheet as proof of their study. Then, students took a test/quiz individually without assistance from other students. Finally, their test scores are compared with those obtained on previous tests. The average score improvement of all over members in team used as team score that can be categorized as a good, excellent or great team. The results of the study stated that the average pretest score obtained by students was 66 and the post-test results increased to 74. In addition, the results of the study also showed that students' enthusiasm in learning English writing was better than before.